Economic development plan and employee participation in public sector in Malaysia - Badariah Ab Rahman; Dzurizah Ibrahim; Rosazman Hussin (OCERINT International, 2016)
Employee Participation (EP) is an important area of research in the field of industrial relations and employment relations. Extensive literature review has argued that EP has the capacity to enhance the quality of decision making by broadening inputs, promotes commitment to the outcomes of the decision making process, improves motivation, cooperation and communication in the workplace. EP also may reduce workloads of supervisors, encourage skill development in the workforce, and can contribute to improved employment relations in general. For that matter, the issue of EP in decision making has attracted the interest among management scholars, industrial relations researchers and managers in organizations as well especially in promoting partnership between employer-employee work relationship. EP has been practiced in the private sector; however there is a broad gap on the importance of EP in the public sector. Therefore, the objective of this paper is to explore on the effectiveness of EP in the public sector from the academic, employers and trade union’s perspectives. The finding of this research has some implication to the industrial relations system and practices in in the public sector in Malaysia.